Human intravital microscopy in the study of sarcomas: an early trial of feasibility - Gabriel, Emmanuel M.; Sukniam, Kulkaew; Popp, Kyle; Bagaria, Sanjay P. (Frontiers in Oncology, 2023)
Sarcomas comprise a vast and heterogenous group of rare tumors. Because of their diversity, it is challenging to study sarcomas as a group with regard to their biological and molecular characteristics. This diverse set of tumors may also possess differences related to their tumor-associated vasculature, which in turn may impact the ability to deliver systemic therapies (e.g., chemotherapy, targeted therapies, and immunotherapy). Consequently, response to systemic treatment may also be variable as these depend on the ability of the therapy to reach the tumor target via the tumor-associated vasculature. There is a paucity of data regarding sarcoma-related tumor vessels, likely in part to the rarity and heterogeneity of this cancer as well as the previously limited ability to imagine tumor-associated vessels in real time. Our group has previously utilized confocal fluorescent imaging technology to observe and characterize tumor-associated vessels in real time during surgical resection of tumors, including cutaneous melanoma and carcinomatosis implants derived from gastrointestinal, gynecological, or primary peritoneal (e.g., mesothelioma) tumors. Our prior studies have demonstrated the feasibility of real-time, human intravital microscopy in the study of these tumor types, leading to early but important new data regarding tumor vessel characteristics and their potential implications on drug delivery and efficacy. In this brief report, we present our latest descriptive findings in a cohort of patients with sarcoma who underwent surgical resection and real-time, intravital microscopy of their tumors. Overall, intravital imaging was feasible during the surgical resection of large sarcomas.